NGELMU: AUGMENTED REALITY-BASED PANJI STORY LEARNING APPLICATION IN GAME-BASED LEARNING AS AN EFFORT TO REVITALIZE CULTURE AND CHARACTER EDUCATION IN ELEMENTARY SCHOOL - Raselly Elfa Putri; Fikry Prastya Syahputra (TALENTA, 2023)
The story of Panji is a form of cultural revitalization that has begun to fade and be displaced by the presence of superheroes who have been adopted from western culture. Unfortunately, the majority of these figures are contrary to the noble values of the Javanese ancestors and are more oriented towards the modernization of western culture. Therefore, this study aims to map the strengths, weaknesses, opportunities and threats of the Ngelmu application which is oriented towards growing interest in learning for elementary school-age children in getting to know Panji Stories and the moral messages it conveys. The results of the study show that Ngelmu has unique and interesting features in increasing students' interest in learning. Among them are: Mirengake, Ngagara, Nyimak, Ngromo, Mitutur. From the results of the analysis, it was concluded that Ngelmu is one of the applications designed to introduce and preserve the Panji Story so that it continues to exist even though the use of technology is classified as increasing. Through this Panji story, users will be introduced to a leader who has noble character and manners in accordance with the teachings of Javanese culture. In addition, this application aims to make the younger generation familiar with original Indonesian heroes before they admire superheroes from western countries.